Regularities of the Dynamics of the Average Width of the Leaves of Silver Birch Near the Maximum Growth in the Vegetation Period - Matveevich Mazurkin, Peter; A.I, Kudryashova (European Journal of Applied Sciences, 2019)
It is shown that the achievement of the maximum of the average width of the birch leaves is a great bioindicator of environmental quality. Moreover, the quality assessment can be carried out without measuring the concentration of pollution. According to patent 2606189 for the invention on the side at an altitude of 1.5 -2.0 m from the prevailing winds on the dynamics from July 27 to September 23, 2018, the average width of 10 leaves near the road was measured. The parameters of the model with two components showed that the half-period of oscillation at the beginning of the growing season for 10 birches varies from 1.32 to 21.35 days. All models of dynamics are the same in design, but have a different character. The growing season near the maximum growth affects with a correlation coefficient of more than 0.999, so the behavior of 10 leaves has a high quantum certainty. To assess the behavior of groups of leaves, a new criterion was introduced – the coefficient of dynamism equal to the ratio of the difference between the fact and the trend to the fact of the average width of the leaves of the birch. The maximum width of the leaves and gave the highest values of the coefficient of dynamism. This criterion allows to rank the birch in descending order of the influence of vibrations from affecting the surrounding of the birch environment.